The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31893/jabb.20038
|View full text |Cite
|
Sign up to set email alerts
|

Scientific findings related to changes in vascular microcirculation using infrared thermography in the river buffalo

Abstract: The objective of this review article is to discuss and analyze the most important scientific findings from studies of vascular microcirculation in the river buffalo using infrared thermography (IRT), as well as the thermal windows utilized with this species. The goals are to define the scope and areas of opportunity for IRT use in evaluating physiological processes and identifying potential applications in reproductive events associated with andrological traits in males and the detection of estrus and udder he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
(60 reference statements)
3
28
1
Order By: Relevance
“…However, it is suggested that evaluations of infrared radiation in river buffaloes need to consider uncontrolled productive and climatic conditions because, in this species, environmental temperatures and changes in respiratory patterns can alter the thermal response of this window [28]. In addition, but from an anatomical perspective, differences between these species must be considered when examining IRT images since the river buffalo's mammary tissue has more prominent suspensory ligaments and longer keratinized teats [30,75]. Some studies of river buffaloes have questioned the use of this region for detecting mastitis because, according to Machado et al [70], radiometric thermal images of the left and right regions of the rear udder present higher correlations with somatic cell counts compared to anterior sections.…”
Section: Udder Region (Regio Uberis) and Mammary Glandmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is suggested that evaluations of infrared radiation in river buffaloes need to consider uncontrolled productive and climatic conditions because, in this species, environmental temperatures and changes in respiratory patterns can alter the thermal response of this window [28]. In addition, but from an anatomical perspective, differences between these species must be considered when examining IRT images since the river buffalo's mammary tissue has more prominent suspensory ligaments and longer keratinized teats [30,75]. Some studies of river buffaloes have questioned the use of this region for detecting mastitis because, according to Machado et al [70], radiometric thermal images of the left and right regions of the rear udder present higher correlations with somatic cell counts compared to anterior sections.…”
Section: Udder Region (Regio Uberis) and Mammary Glandmentioning
confidence: 99%
“…These conditions exist, for example, in the eye of the orbital region ( regio orbitalis ) [ 34 , 35 ], the auricular pavilion of the ear in the auricular region ( regio auricularis ), or are traversed by large, straight vessels, as in the tail region ( regio caudalis ) of rats. Regions that satisfy these requirements are called thermal windows [ 16 , 30 , 36 , 37 ]. The high density of blood vessels near the dermal surface is critical because modifications of their diameter affect blood flow and change the heat exchange rate in the zone [ 38 ].…”
Section: Anatomical Locations Of Thermal Windows In Cattle and River Buffalomentioning
confidence: 99%
See 2 more Smart Citations
“…However, during the bacterial challenge, endothelial cells redirect some of their lactation function by initiating inflammation to protect the underlying tissue from injury. Endothelial cells closely control the passage of plasma components and leukocytes into infected tissue at the start of inflammation [3]. The discovery of the active role of endothelium has led to significant progress in the study of the pathogenesis of cardiovascular diseases [4].…”
Section: Introductionmentioning
confidence: 99%